Two new species of Sternaspis Otto, 1821 (Polychaeta: Sternaspidae) from China seas - Wu, Xuwen; Salazar-Vallejo, Sergio I.; Xu, Kuidong (Zootaxa, 2015)
Two species of Sternaspidae, Sternaspis chinensis sp. nov. and S. liui sp. nov., are described based on historic material and recently collected specimens in the sea areas of China. Sternaspis chinensis is abundantly distributed from the Bohai Sea southwards to the East China Sea. It has been frequently misidentified as the nominally cosmopolitan species S. scutata (Ranzani, 1817) in China since the 1950s. However, S. chinensis differs from the latter by possessing concentric bands on the shield (vs. absent) and crenulated posterior margin reaching or slightly expanded beyond the posterolateral corners (vs. posterior margin smooth and markedly expanded beyond the posterolateral corners). Sternaspis chinensis most resembles the NE Pacific species S. affinis Stimpson, 1864, but differs distinctly by its markedly concentric bands decorated from margin to center (vs. mainly restricted in the marginal area). Sternaspis liui is characterized within the genus by its slightly soft shield with firmly adhered sediment particles, which gives it a superficial resemblance to species of Caulleryaspis Sendall & Salazar-Vallejo, 2013. However, the shields of the latter are remarkably soft and poorly developed, without ribs and concentric lines, while in Sternaspis liui both the ribs and concentric lines are well defined. Variations of both species with remarks on juvenile shield development are provided.